1996
DOI: 10.1046/j.1365-3024.1996.d01-137.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential antibody recognition of FC27‐like Plasmodium falciparum merozoite surface protein MSP2 antigens which lack 12 amino acid repeats

Abstract: Three alleles of the FC27-type allelic family of the MSP2 gene of the malaria parasite Plasmodium falciparum have been sequenced from parasites from the field (The Gambia and Tanzania). These alleles lack the 12 amino acid repeat units which are usual in this family of MSP2 alleles. We have investigated the recognition by sera from an endemic area (The Gambia) of three recombinant MSP2 proteins that have 5, 1 and no copies of this repeat region. Antibody recognition of these recombinant proteins varied accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…The major serological subdivision of the FC27-like alleles was between those that contain multiple 32-mer repeats and single (or no) 12-mer repeats (groups 1 and 2 in Table 2) and those that contain a single 32-mer repeat and multiple 12-mer repeats (group 3). Within group 3, differences in the number of 12-mer repeats seriously affected the avidity of antibody binding, confirming our previous observations (27) These data provide evidence in support of the immune selection hypothesis for the FC27 family of msp-2 alleles. However, the number of "strains" or serogroups appears to be rather limited (perhaps as few as 2 or 3), with each serogroup comprising multiple cross-reactive variants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The major serological subdivision of the FC27-like alleles was between those that contain multiple 32-mer repeats and single (or no) 12-mer repeats (groups 1 and 2 in Table 2) and those that contain a single 32-mer repeat and multiple 12-mer repeats (group 3). Within group 3, differences in the number of 12-mer repeats seriously affected the avidity of antibody binding, confirming our previous observations (27) These data provide evidence in support of the immune selection hypothesis for the FC27 family of msp-2 alleles. However, the number of "strains" or serogroups appears to be rather limited (perhaps as few as 2 or 3), with each serogroup comprising multiple cross-reactive variants.…”
Section: Discussionsupporting
confidence: 90%
“…The 32-mer and 12-mer repeats vary in number (12-mer repeats being completely absent in some sequences), and minor sequence differences occur within the repeats (Table 2). The number of 12-mer repeats can affect the avidity of antibody binding (27). All alleles shown in Table 2 share a conserved 12-aa sequence (ESSSSGNAPNKT) at the C terminus and a conserved 7-aa sequence (ADTPTAT) between the 32-mer and 12-mer repeats.…”
Section: Resultsmentioning
confidence: 99%
“…13 In addition, three sequence classes of the amplified block 2 of the MSP-1 gene, denoted K1, MAD20, and RO33, 14 and two of block 3 of the MSP-2, denoted IC1 and FC27, were identified by sequence-specific probes hybridized to Southern blots of the PCR-amplified fragments. 15 In addition, a probe was used that recognizes alleles of the FC27 form of MSP-2 that lacks the 12 amino acid repeat 16 denoted SUD (5Ј-GTTCA-AGTTCTGGCAATGCA-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] Many studies have identified the presence of B-cell epitopes in the repeats of circumsporozoite protein (CSP), liver stage antigen-1 (LSA-1), and merozoite surface protein-2 (MSP-2) of P. falciparum. [13][14][15][16] These antigens are also vaccine candidate antigens against sporozoite, liver, and blood stage parasites, respectively. In vitro studies have revealed that antibodies directed against the CSP repeats can inhibit sporozoite invasion into cultured liver cells and administration of such antibodies can completely protect mice and monkeys against sporozoite-induced malaria.…”
Section: Introductionmentioning
confidence: 99%